Clear Cell Carcinoma of the Penis: An HPV-related Variant of Squamous Cell Carcinoma. (July 2016) - Sanchez, Diego F.; Rodriguez, Ingrid M.; Piris, Adriano; Cañete, Sofía; Lezcano, Cecilia; Velazquez, Elsa F.; Fernandez-Nestosa, Maria J.; Mendez-Pena, Javier E.; Hoang, Mai P.; Cubilla, Antonio L.
Abstract : Penile clear cell carcinoma originating in skin adnexal glands has been previously reported. Here, we present 3 morphologically distinctive penile tumors with prominent clear cell features originating not in the penile skin but in the mucosal tissues of the glans surface squamous epithelium. Clinical and pathologic features were evaluated. Immunohistochemical stains were GATA3 and p16. Human papilloma virus (HPV) detection by in situ hybridization was performed in 3 cases, and whole-tissue section-polymerase chain reaction was performed in 1 case. Patients' ages were 52, 88, and 95 years. Tumors were large and involved the glans and coronal sulcus in all cases. Microscopically, nonkeratinizing clear cells predominated. Growth was in solid nests with comedo-like or geographic necrosis. Focal areas of invasive warty or basaloid carcinomas showing in addition warty or basaloid penile intraepithelial neoplasia were present in 2 cases. There was invasion of corpora cavernosa, lymphatic vessels, veins, and perineural spaces in all cases. p16 was positive, and GATA3 stain was negative in the 3 cases. HPV was detected in 3 cases by in situ hybridization and in 1 case by polymerase chain reaction. Differential diagnoses included other HPV-related penile carcinomas, skin adnexal tumors, and metastatic renal cell carcinoma. Features that support primary penile carcinoma were tumor location, concomitant warty and/or basaloid penile intraepithelial neoplasia, and HPV positivity. Clinical groin metastases were present in all cases, pathologically confirmed in 1. Two patients died from tumor dissemination at 9 and 12 months after penectomy. Clear cell carcinoma, another morphologic variant related to HPV, originates in the penile mucosal surface and is probably related to warty carcinomas.